2010
DOI: 10.1111/j.1600-0560.2009.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Lymphoplasmacellular mucositis‐dermatitis

Abstract: A uniform nomenclature for ZLL does not exist. Based on the results of this analysis, we suggest that the generic term idiopathic lymphoplasmacellular mucositis-dermatitis be considered to encompass the lymphoplasmacellular infiltrates in the skin and mucosal surfaces considered herein. This designation is morphologically descriptive and can be applied regardless of anatomic location.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 31 publications
(37 reference statements)
2
40
0
5
Order By: Relevance
“…The mean age at onset of vulvar lichen sclerosus (VLS) in our population was about 49 years, which is consistent with other reports, although the condition has been reported in the third to ninth decade of life [1,2,3,4,5] and a unique case has been described in an 8-year-old-girl [25]. …”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The mean age at onset of vulvar lichen sclerosus (VLS) in our population was about 49 years, which is consistent with other reports, although the condition has been reported in the third to ninth decade of life [1,2,3,4,5] and a unique case has been described in an 8-year-old-girl [25]. …”
Section: Discussionsupporting
confidence: 79%
“…The incidence of PCV is unknown, as well as its aetiopathogenesis, although a variety of triggering factors have been hypothesized [1,2,3,4,5,19]. The presence of a lichenoid infiltrate containing a predominance of plasma cells as a distinctive histological marker suggests a polyclonal stimulation of B cells [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dans l'un de ces trois cas, une maladie de Bowen était suspectée cliniquement et le diagnostic histologique était finalement rassurant puisqu'il infirmait ce diagnostic pour orienter vers une dermatose inflammatoire et non pas tumorale. L'infiltrat inflammatoire est plus souvent d'intensité modérée dans la balanite de Zoon, par comparaison à la vulvite de Zoon, et il peut exister une fibrose du derme superficiel, ces deux caractéristiques histologiques pouvant effectivement poser un problème de diagnostic différentiel entre balanite de Zoon et lichen scléreux de type inflammatoire [9]. Enfin, dans un cas, une kératose séborrhéique ne pouvait être distinguée histologiquement d'un condylome.…”
Section: Discussionunclassified
“…However, there are cases of PCV with minimal plasma cells [9].Thus, it is important to know the other characteristics seen on biopsy. Other histologic features of PCV include 'lozenge shaped' (diamond shaped) keratinocytes, spongiosis with vascular dilatation, and hemosiderin deposition [2][3][4][5][6][7][10][11][12][13][14]. Though, one retrospective evaluation of PCV biopsy specimens reported that "lozenge-shaped" keratinocytes were rarely seen [9].…”
Section: Case Reportmentioning
confidence: 99%